Discovery of high-pressure post-perovskite phase in HoCrO3. (January 2023) - Mall, Ashish Kumar; Garg, Nandini; Verma, Ashok K.; Errandonea, Daniel; Chitnis, Abhishek V.; Srihari, Velaga; Gupta, Rajeev
Abstract: By employing both experimental and theoretical methods, we investigated the high-pressure structural aspects of HoCrO3 up to 100 GPa. We found by the first-time evidence of a perovskite-to-post-perovskite transformation in an orthochromite. X-ray diffraction measurements showed that the ambient orthorhombic perovskite phase starts transforming to the post-perovskite phase at ∼20 GPa. However, the ambient phase does not completely transform to perovskite even at 75 GPa. The large coexistence between both phases is assigned to the effect of kinetic barriers. The conclusions extracted from x-ray diffraction agree well with density-functional theory. Raman spectroscopy also supports the observed phase transition. Discontinuities in mode frequencies, changes in the slope of the pressure dependency of frequencies, and changes in mode intensities were observed near ∼20 GPa, i.e. at the transition pressure. Our studies also demonstrated that even at 100 GPa Cr–O–Cr distortions are not sufficient to raise the Néel temperature of HoCrO3 to 300 K. Our analysis showed that the bulk modulus of the perovskite phase is B0 = 269(15) – 298(15) GPa with a pressure derivative, B 0 ′ = 4.2(9) – 4.7(9) being HoCrO3 one of the less compressible known perovskites. Our work suggests that the post-perovskite phase could be stabilized in other orthochromites also by high-pressure treatment. Graphical abstract: Image 1 Highlights: High pressure structural transition is studied using XRD, Raman and DFT for HoCrO3 . A perovskite to post-perovskite phase transition is observed at high pressure. The post-perovskite phase can be retained on full release of pressure. Polyhedral compressibility cannot be estimated solely by dω/dP data . Even 100 GPa CrOCr distortions are insufficient to raise Néel temperature to 300 K.